DEVELOPING A GOVERNANCE MODEL FOR SOUVENIR MSMES AND SOUVENIR CENTERS - Lubis, Tona Aurora; Firmansyah, Firmansyah; Solikhin, Agus; Fitriaty, Fitriaty; Ningsih, Maryati (jfpublisher, 2025)
This study explores the relationship between MSME souvenir governance and souvenir center governance in the context of supporting regional tourism in Jambi Province, Indonesia. The research addresses the challenges faced by MSME operators in accessing souvenir centers, such as limited skills, high raw material costs, and insufficient marketing knowledge, which hinder the overall tourism experience. To address these issues, this study develops a governance model based on key indicators that influence the efficiency and effectiveness of both MSME vendors and souvenir centers. The study employs a quantitative research approach, using purposive sampling to gather data from 100 MSME operators and souvenir center managers. The data is analyzed using Structural Equation Modeling (SEM) with SmartPLS software to evaluate the relationship between governance variables. The findings reveal that Product Quantity is the most influential factor in MSME souvenir governance, indicating that business actors must focus on maintaining consistent product supply. Meanwhile, Distance is the most significant indicator for souvenir center governance, highlighting the importance of strategic locations to attract customers. The study concludes that the governance practices of MSME souvenir vendors positively impact the governance of souvenir centers. This research provides valuable insights into improving governance structures in the souvenir industry, promoting better collaboration between MSME vendors and souvenir centers to support sustainable business growth.